The Impact of RSV-Associated Respiratory Disease on Children in Asia - Divarathne, Maduja Vyanga Manike; Ahamed, Rukshan Rafeek; Noordeen, Faseeha (Journal of Pediatric Infectious Diseases, 2019)
Acute respiratory tract infections (ARTIs) are leading contributors to the global infectious disease burden, which is estimated to be 112,900,000 disability adjusted life years. Viruses contribute to the etiology of ARTIs in a big way compared with other microorganisms. Since the discovery of respiratory syncytial virus (RSV) 61 years ago, the virus has been recognized as a major cause of ARTI and hospitalization in children. The morbidity and mortality attributable to RSV infection appear to be higher in infants < 3 months and in those with known risk factors such as prematurity, chronic lung, and congenital heart diseases. Crowded living conditions, exposure to tobacco smoke, and industrial or other types of air pollution also increase the risk of RSV-associated ARTI. Many epidemiological studies have been conducted in developed countries to understand the seasonal patterns and risk factors associated with RSV infections. Dearth of information on RSV-associated morbidity and mortality in Asian and developing countries indicates the need for regional reviews to evaluate RSV-associated disease burden in these countries. Epidemiological studies including surveillance is the key to track the disease burden including risk factors, seasonality, morbidity, and mortality associated with RSV infection in these countries. These data will contribute to improve the clinical diagnosis and plan preventive strategies in resource-limited developing countries.
Keywords: acute respiratory tract infections; respiratory syncytial virus; epidemiology; children; Asia